2018
DOI: 10.31002/ijose.v2i1.583
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Science Learning Using Scientific Approach in Junior High Schools in Semarang Regency

Abstract: The scientific approach is strongly suggested to be used in implementing "Curriculum of 2013" (K13) by Department of Education. This study aimed to identify whether integrated science learning was implemented in Junior High Schools in the Semarang Regency, Indonesia used a scientific approach, how it was implemented, and what problems that emerged in it. This research was conducted in 13 Junior High Schools in Semarang Regency, Central Java Province that implemented K13 during the odd semester in 2016/2017 sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The probing prompting technique and the scientific approach to learning outcomes had a very strong positive and substantial relationship [20]. Students' abilities in the areas of cognition, motor skills, and curiosity (scientific attitudes) could be enhanced by using a scientific approach [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The probing prompting technique and the scientific approach to learning outcomes had a very strong positive and substantial relationship [20]. Students' abilities in the areas of cognition, motor skills, and curiosity (scientific attitudes) could be enhanced by using a scientific approach [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2013 curriculum, learning in physics must use the scientific method, which contains five components: observing, asking, exploring, concluding and communicating. (Sudjito, Keliat & Hastuti 2018;Suyanto 2018). Scientists build physical science, which is part of science through a process that begins with observing natural phenomena, followed by empirical investigations, and ends with conclusions that usually produce concepts, laws, principles, or even theories.…”
Section: Introductionmentioning
confidence: 99%
“…The development of scientific literacy can be built by developing literacy by reading, writing, and discussing (Setyaningrum, 2014;Tomas & Ritchie, 2014;Pelger & Nilsson, 2015). Van Zee, et al (2013); Wibowo (2018); Allison & Goldston (2018); Sudjito, et al (2018) also revealed that literacy could also be developed through aspects of learning containing scientific literacy.…”
Section: Introductionmentioning
confidence: 99%